2017
DOI: 10.32404/rean.v4i5.2165
|View full text |Cite
|
Sign up to set email alerts
|

Bactérias Fixadoras De Nitrogênio E Molibdênio No Cultivo Do Amendoim Em Solo Do Cerrado

Abstract: O uso de práticas agrícolas sustentáveis que otimizem a fixação biológica de nitrogênio (FBN) pela cultura do amendoim são importantes para assegurar elevados níveis de produtividade. Portanto, neste estudo objetivou-se avaliar a eficiência da aplicação de molibdênio e da coinoculação das sementes com Bradyrhizobium japonicum e/ou Azospirillum brasilense na nodulação, no crescimento e na partição de matéria seca das plantas de amendoim (Arachis hypogaea L., cv. IAC Tatu ST). As plantas foram cultivadas em vaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
2
2
1
3
Order By: Relevance
“…These results differ from those reported by Santos et al (2017), who did not find significant difference between the control treatment and single or combined inoculation with B. japonicum and A. brasilense for the number of branches per plant in the peanut cultivar IAC Tatu ST.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…These results differ from those reported by Santos et al (2017), who did not find significant difference between the control treatment and single or combined inoculation with B. japonicum and A. brasilense for the number of branches per plant in the peanut cultivar IAC Tatu ST.…”
contrasting
confidence: 99%
“…Similar results were obtained by Santos et al (2017), who found that single and combined inoculation with B. japonicum and A. brasilense influenced the number of leaves of peanut plants. This is because nitrogen is closely linked to the photosynthetic process, as it is a component of the chlorophyll molecule (LIN et al, 2009).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Efeito do tamanho das sementes e do tratamento de inoculação com Bradyrhizobium japonicum e/ou Azospirillum brasilense na porcentagem de emergência, no índice de velocidade de emergência e no tempo médio de emergência das plântulas de amendoim (Arachis hypogaea L., cv. IAC Tatu ST) em um solo arenoso do Cerrado sob condições de casa de vegetação Santos et al (2017), os quais concluíram que a coinoculação das sementes de amendoim com B. japonicum e A. brasilense pode proporcionar sustentabilidade para o sistema de produção de amendoim na região do Cerrado por melhorar a nodulação das raízes e a fixação biológica de nitrogênio.…”
Section: Nodulação Radicular Do Amendoimunclassified
“…Bacteria of the genus Azospirillum are the most frequently used PGPR in Brazil and worldwide (Bulegon et al., 2017; Hungria, Nogueira, & Araujo, 2015; Marks, Megías, Nogueira, & Hungria, 2013), but little is known about their interaction with rhizobia when both are applied on peanut seeds (Santos, Bush, Silva, Zuffo, & Steiner, 2017). Recent research results have proven the beneficial effects of co‐inoculation of rhizobia and Azospirillum brasilense on nodulation, N acquisition, and growth of leguminous plants, especially on soybeans and common beans (Bulegon et al., 2017; Chibeba et al., 2015, Hungria et al., 2015; Steiner, Ferreira, & Zuffo, 2019).…”
Section: Introductionmentioning
confidence: 99%